Investigation of antioxidant activity in maize during low temperature stress - Janda, Tibor (Acta Biologica Szegediensis, 2005)
Young maize inbred lines and their hybrids were tested for chilling tolerance using the chlorophyll fluorescence induction technique. The genotypes were ranked based on the decrease in the Fv/Fm parameter after chilling stress at 5°C. The activities of certain antioxidant enzymes were determined in control and cold-treated plants. The results suggest that although there are differences between the genotypes in the activities of almost all the antioxidant enzymes, these differences do not reflect the differences in chilling tolerance.